Faktor-Faktor yang Menentukan Pendapatan Asli Daerah pProvinsi Sumatera Barat Menggunakan Analisis Regresi Data Panell - cici amelia; helma helma (Journal of Mathematics UNP, 2019)
Abstract–Original Local Government Revenue(OLGR) is a component of regional financial resources collected under the laws and regulations in the area. It increased in each Regency / City of West Sumatra Province when 2008 to 2017, but may decreased in certain years. This research discusses about the factors that determine the Original Local Government Revenue(OLGR) of West Sumatra Province. The data used in this research obtained from the publication of the West Sumatra Central Bureau of Statistics (CBS) which supported by each Regency / City in 2008 to 2017. Results of the research that used regression analysis are data panel factor local tax (x2)(x2) and issued by the local government (x4) to be the most determining factor for OLGR in group I. Factors in population (x1), local tax (x2), regional retribution (x3) and local government (x4) are the most determining factors for OLGR in groups II. Local tax factor (x2), regional retribution (x3), local government (x4) and economic growth rate (x5) are the factors that most determine OLGR for group III. Keywords–OLGR, Panel Data Regression Analysis, Fixed Effect Model, Hausman Thest.